Highly efficient transduction and expression of cytokine genes in human tumor cells by means of autonomous parvovirus vectors; generation of antitumor responses in recipient mice - Haag, Andreas; Dinsart, Christiane; Rommelaere, Jean (Human gene therapy, 2004)
The possible use of recombinant autonomous parvoviruses as vectors to efficiently express therapeutic cytokines in human tumor cells was evaluated in vitro and in vivo. The parvovirus H1 was used to generate recombinant viruses (rH1) that carried transgenes encoding either human interleukin 2 (IL-2) or monocyte chemotactic protein 1 (MCP-1), in replacement of part of the capsid genes. Such rH1 viruses have been shown to retain in vitro the intrinsic oncotropic properties of the parental virus. On infection with the recombinant viruses at an input multiplicity of 1 replication unit (RU) per cell, HeLa cultures were induced to release 4-10 mug of cytokine per 106 cells over a period of 5 days. The expression of the rH1-transduced human cytokine/chemokine could also be detected in tumor material recovered from nude mice that had been subcutaneously engrafted with in vitro-infected HeLa cells. The formation of tumors from HeLa xenografts was reduced by 90% compared with wild-type or mock-infected cells as a result of cells preinfected with IL-2-expressing virus at an input multiplicity as low as 1 RU per cell. Tumors arising from HeLa cells infected with transgene-free or MCP1-expressing vectors or with wild-type H1 virus were not rejected at this virus dose. Tumors infected with rH1/IL-2 virus displayed markers indicative of their infiltration with NK cells in which the cytocidal program was activated, whereas little NK activity was detected in wild-type virus or mock-infected tumors. Altogether, these data show that the IL-2 expressing H1 vector was a more potent antineoplastic agent than the parental virus, and point to the possible application of recombinant autonomous parvoviruses toward therapy of some human tumors.
Elektronische Reproduktion der Druckausgabe
Gesehen am 12.02.2021